Expressão de isoformas do gene VEGF e de proteínas reguladoras de splicing em carcinoma espinocelular de cabeça e pescoço - Chicote, Patricia Matos Biselli (2011)
Tumor growth and progression depend on angiogenesis, a process that involves the formation of new blood vessels from a preexisting vascular endothelium. Vascular endothelial growth factor (VEGF) is a potent mitogen for endothelial cells and its overexpression is associated with tumor growth and metastasis. However, the selection of a alternative splicing site at the end of the exon 8 of VEGF gene results in a sister-family of isoforms, VEGFxxxb, that seems to have anti-angiogenic proprieties. Objectives: The aim of this work was to quantitatively analyze the expressions of VEGF gene isoforms generated by alternative splicing in samples of head and neck squamous cells carcinoma and adjacent normal tissues, and to determine the effect of regulatory proteins in the control of VEGF gene splicing. Methods: The levels of VEGFxxx e VEGFxxxb mRNA and the splicing regulatory proteins SRp55, SRp40, ASF/SF2 and SRPK1 were quantified by real time quantitative PCR. Results: The overexpression of both VEGF isoforms (VEGFxxx and VEGFxxxb) was observed in head and neck squamous cells carcinoma related to normal tissue samples. A positive correlation between VEGFxxx and VEGFxxxb expression was observed in head and neck tumors. Splicing factor ASF/SF2 presented higher expression in tumors when compared to normal tissues. Pharynx tumors presented overexpression of VEGFxxx. VEGFxxxb was underexpressed in oral cavity tumors. Overexpression of both VEGF isoforms was observed in aggressive tumors. There was a positive correlation among ASF/SF2, SRp55 and SRp40 proteins and both VEGF isoforms, and among SRPK1 protein and ASF/SF2, SRp55 and SRp40 in tumor tissues. Conclusions: The results suggest that both VEGF isoforms play a role in angiogenesis promotion in head and neck tumors. VEGF isoforms present differential expression related to the anatomic sites of tumor and tumor aggressiveness. ASF/SF2, SRp55 and SRp40 proteins are involved in the regulation of the VEGF gene splicing mechanism.